PERTANGGUNGJAWABAN HUKUM PEMILIK MANFAAT (BENEFICIAL OWNER) DI PERUSAHAAN INDONESIA - Aninta Sagitaria (Fakultas Hukum Universitas Muhammadiyah Palu, 2022)
This research studies about the concepts of the beneficial owner, their legal liabilities and disclosure according Indonesia’s law and regulations. The research method is using normative method that examines the internal aspects of the law and bases its analysis on the prevailing laws and regulations and is relevant to the problem being studied. The data used is secondary data in the form of library data derived from basic regulations and laws and regulations relevant to the research topic, books, and legal journals related to the research topic. The results of this study indicate that the beneficial owners are the parties who receive the benefits and are able to exercise absolute control over the corporation and there are five methods used to identify the beneficial owners. Legal arrangements related to the introduction and disclosure of beneficial owner are regulated in Peraturan Presiden Nomor 13 Tahun 2018 about Penerapan Prinsip Mengenali Pemilik Manfaat Dari Korporasi Dalam Rangka Pencegahan dan Pemberantasan Tindak Pidana Pencucian Uang dan Tindak Pidana Pendanaan Terorisme. The regulation contains the criteria for the beneficial owner and the mechanism for reporting the beneficial owner to the parties concerned. In relation of their legal liabilities, there are three parameters from beneficial owners, which are consist of: Ultimate power, economic benefit, and control. According to Indonesia’s Penal Code Article 55, beneficial owners can be held accountable by expanding what they did and what their intentions were.